Systematic review search methods evaluated using the Preferred Reporting of Items for Systematic Reviews and Meta-Analyses and the Risk Of Bias In Systematic reviews tool. (7th December 2020) - de Kock, Shelley; Stirk, Lisa; Ross, Janine; Duffy, Steven; Noake, Caro; Misso, Kate
Abstract: Objectives: To evaluate the methodological and reporting characteristics of search methods of systematic reviews (SRs) using the Preferred Reporting of Systematic Reviews and Meta-Analyses (PRISMA) checklist and the Risk Of Bias In Systematic reviews (ROBIS) tool. Methods: A sample of 505 SRs published in 2016 was taken from KSR Evidence, a database of SRs, and analyzed to assess compliance with Information sources and Search of the PRISMA checklist. Domain 2 (D2) (Identification and Selection of Studies) of the ROBIS tool was used to judge the risk of bias in search methods. Results: Regarding Information sources and Search of PRISMA, twenty percent of SRs which claimed to be PRISMA-compliant in their methods, were compliant; twenty-four percent of SRs published in journals that require PRISMA reporting were compliant; nineteen percent in total were found to be compliant. Twenty-eight percent of SRs were judged to be at a low risk of bias in D2 and so searched widely with an effective strategy and, finally, ten percent were both compliant with the reporting of Information sources and with Search of PRISMA and were judged to be at a low risk of bias in D2. Conclusions: Ninety percent of SRs are failing to report search methods adequately and to conduct comprehensive searches using a wide range of resources. Editors of journals and peer reviewers need to ensure that they understand the requirements of PRISMA and that compliance is adhered to. Additionally, the comprehensiveness of search methods for SRs needs to be given more critical consideration.